The caribbean: geopolicts and geohistory - Morse, Richard M. (Revista de História, 1975)
Pan-Caribbeanism — whether as a policy aspiration, as scientificconjecture, or as sentimental indulgence — is an increasingly familiarby-product of the Caribbean crucible of new and self-renovating nations.Any politician who pursues the goal of Caribbean federation,however, or any social scientist who generalizes about Caribbean societiesis forced to recognize that hitherto the only focused and authoritativeregional perspectives have been geopolitical and externally imposed.Ironically, the persons and powers who adopted them areprecisely those responsible for the region's fragmentation, for its neutralizationagainst internal schemes of integration.